THE EFFECT OF THINK PAIR SHARE TECHHNIQUE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Nurmahyuni Asrul (Journal MELT (Medium for English Language Teaching), 2019)
This study was aimed to investigate the effect of applying Think Pair Share technique on student’s reading comprehension. This study was a quantitative study with pre-test and post-test experimental design. There were two variables in which the independent variable was Think Pair Share technique and the dependent variable was reading comprehension. This study was conducted at SMA Harapan 3 Deli Serdang.  The population was the grade X students with the total number of students were 145. The sample of this study was the class Xips1 and Xips2 with the total number of samples were 60. The samples were divided into two groups, they were experimental group and control group and each group was consisted of 30 students. The experimental group will taught by using Think Pair Share technique and the control group will taught by using the conventional technique. Both group will given pre-test and post-test to obtain the data. The data will be analyzed by using t-test formula. It was obtained that tobs (t-observed) was higher than t-table(t-table) in which tobs = 8,8461 > ttable = 2,021 with the level of significant was 0,05 (5%) and the df (degree of freedom) = (Na + Nb – 2 = 30 + 30 -2 = 58). It showed that Ha (hypothesis alternative) was accepted and Think Pair Share technique affected students’ reading comprehension.